Test and analysis of multi-cavity particle damper for vertical vibration control of pipeline structures. (15th April 2023) - Wang, Baoshun; Wang, Haishen; He, Zhizhou; Liu, Dayou; Pan, Peng
Highlights: Proposing a new type of particle damper for vertical vibration control of pipeline structures, the MPD. Solving the MPD mechanical model by analytical solution and numerical simulation. Proposing the optimization method of MPD. Proving the rationality and correctness of analytical solution, simulation, and optimization by shaking table test. Analyzing the damping mechanism of MPD. Abstract: Pipeline structures vibrate violently in the excitation resonance region owing to their high vibration frequency and small damping, which may result in machine shutdowns, fatigue failure, fluid leakage, and occasionally catastrophic explosions. Particle damping technology has the potential for the control of high-frequency vibration. However, research on particle damping technology for controlling the vibration of pipeline structures is limited, particularly with regards to the control of vertical vibration. The existing particle dampers are not appropriate for pipeline vibration control; therefore, this study developed a novel particle damper called the multi-cavity particle damper (MPD). Herein, the details of the MPD are first introduced and the mechanical model for an MPD-controlled pipeline under vertical vibration is presented. The mechanical model was solved theoretically for the case with two symmetric impacts per cycle, and the simulation was conducted for a general case. The MPD was optimized based on the analytical solution. Shaking table tests were carried out for the MPD-controlled pipeline subjected to harmonic excitation to verify the damping effect of the MPD under vertical vibration. The damping mechanism of the MPD under vertical vibration is discussed. The results reveal that the MPD exerted a significant damping effect on the vertical vibration of the pipeline structure in a wide frequency range, and reduced the vibration amplitude of the pipeline by 97.54%. The analytical solution, simulation, and optimization methods were validated by a shaking table test.